Distinct fecal microbial signatures are linked to sex and chronic immune activation in pediatric HIV infection - Rosel-Pech, Cecilia; Pinto-Cardoso, Sandra; Chávez-Torres, Monserrat; Montufar, Nadia; Osuna-Padilla, Iván; Ávila-Ríos, Santiago; Reyes-Terán, Gustavo; Aguirre-Alvarado, Charmina; Matías Juan, Norma Angelica; Pérez-Lorenzana, Héctor; Vázquez-Rosales, José Guillermo; Bekker-Méndez, Vilma Carolina (Frontiers in Immunology, 2023)
Introduction Our understanding of HIV-associated gut microbial dysbiosis in children perinatally-infected with HIV (CLWH) lags behind that of adults living with HIV. Childhood represents a critical window for the gut microbiota. Any disturbances, including prolonged exposure to HIV, antiretroviral drugs, and antibiotics are likely to have a significant impact on long-term health, resulting in a less resilient gut microbiome. The objective of our study was to characterize the gut microbiota in CLWH, and compare it with HIV-unexposed and -uninfected children. Methods We enrolled 31 children aged 3 to 15 years; 15 were CLWH and 16 were HUU. We assessed dietary patterns and quality; quantified soluble and cellular markers of HIV disease progression by flow cytometry, enzyme-linked immunosorbent and multiplex-bead assays, and profiled the gut microbiota by 16S rRNA sequencing. We explored relationships between the gut microbiota, antibiotic exposure, dietary habits, soluble and cellular markers and host metadata. Results Children had a Western-type diet, their median health eating index score was 67.06 (interquartile range 58.76-74.66). We found no discernable impact of HIV on the gut microbiota. Alpha diversity metrics did not differ between CLWH and HUU. Sex impacted the gut microbiota (R-squared= 0.052, PERMANOVA p=0.024). Male children had higher microbial richness compared with female children. Two taxa were found to discriminate female from male children independently from HIV status: Firmicutes for males, and Bacteroides for females. Markers of HIV disease progression were comparable between CLWH and HUU, except for the frequency of exhausted CD4+ T cells (PD-1+) which was increased in CLWH (p=0.0024 after adjusting for confounders). Both the frequency of exhausted CD4+ and activated CD4+ T cells (CD38+ HLADR+) correlated positively with the relative abundance of Proteobacteria (rho=0.568. false discovery rate (FDR)-adjusted p= 0.029, and rho=0.62, FDR-adjusted p=0.0126, respectively). Conclusion The gut microbiota of CLWH appears similar to that of HUU, and most markers of HIV disease progression are normalized with long-term ART, suggesting a beneficial effect of the latter on the gut microbial ecology. The relationship between exhausted and activated CD4+ T cells and Proteobacteria suggests a connection between the gut microbiome, and premature aging in CLWH.